A Logical Interpretation of the Nefyü'l-Medârik Method in the Usul of Fiqh - Kantar, Muhammet (Fırat University, 2024)
In the fiqh? doctrine, the issue of nafy al-mad?rik does not find a place for itself with this very nomenclature, and in the classical approach, it is often referred to by different names, but we have found it appropriate to use this term in order to make the subject more understandable and to lead to a more practical use of the expression rather than a sentence. One of the main reasons why we find the subject worthy of research is that there are almost no independent and original studies on it. Another reason was to determine the relationship between the two, since those who frequently and openly do not give it a chance examine it under the title of istish?b. In the process, our multidisciplinary reading tendency led us to realize how similar some of the terminological expressions that appear in modern logic are. In Islamic legal methodology, the method of “absence of evidence/nafy al-mad?rik”, which plays an important role in the knowledge of basic methods for experts who will deduce religious rulings from the relevant sources, is mostly discussed together with the evidence of istish?b and not analyzed in a separate context. In the absence of evidence that would constitute the ruling on any subject, jurists have mentioned this method, which states that there is no ruling because there is no evidence. The issue of the absence of evidence, which is usually analyzed by the Hanaf?s under the heading of fasid evidence, was occasionally used by other jurists. If the absence of evidence does not result in the absence of the ruling, the scholars have resorted to the evidence of istish?b, which is the opinion that the ruling continues to exist. However, as we have mentioned, the mixed treatment of both methods has led to the problem of where they should be positioned in the hierarchical evidence platform and how they should be perceived. The fact that a sixth prayer was not commanded upon the necessity of the existence of the five daily prayers is one of the main examples of the method of nafy. Accordingly, it is possible to rule that the sixth prayer does not exist in the absence of any evidence showing that the legislator did not impose a new one on top of the five rak'ahs and vice versa. In terms of its scope, the issue of the absence of evidence is not only used in classical fiqh. In fact, the breadth of this subject should not be limited to Islamic sciences. In fact, the method of absence of evidence also guides the modern understanding of science. The method in question, which is mostly expressed as the absence of evidence, is rejected by a considerable number of popular acceptance. Science, so to speak, does not see the absence of evidence as a correct approach. A famous and striking example of the absence of evidence is as follows: “There is no evidence for the existence of aliens on Earth, therefore there are no aliens, or aliens do not exist, based on the lack of evidence for this”. In this study, first of all, the elements constituting the phrase “absence of evidence” are analyzed. The method of absence of evidence is discussed together with its debates and parties in terms of the meaning formed as a result of the examination. Its relationship with istish?b has been analyzed in terms of its relevance. In doing so, we have also included whether it is sufficient for the person who claims that the ruling does not exist due to the absence of the relevant evidence to prove his claim in a mere way. While trying to reveal all these, we have also tried to address how correct it is for the person who claims that there is no evidence for the relevant ruling in the method of absence of evidence to make a decision based solely on this. In addition, we have discussed the issue of absence of evidence together with some issues of various disciplines such as kalam and logic due to its relevance. As a result of the discussions, we tried to show that the method of nafy and istishab are not the same thing. Following these, some evaluations were made about the theory of nafys. Among these evaluations, there are some interpretations that are close to the Hanaf?s' stance on this issue and some determinations about the fallacy of nafy in terms of the science of logic. As a result, an independent study on nafy al-mad?r?q has been presented to you, the reader, based on a logical approach to it. However, this attempt will not completely fill the gap in the literature on the subject. We hope that this study will serve as an opportunity for further research to fill the aforementioned gap, and that the subject will reach a wider audience.

Fıkhî doktrinde nefyü’l-medârik meselesi, tam da bu adlandırmayla kendisine çok yer bulamamaktadır ve klasik yaklaşımda daha çok farklı isimlerle anılmaktadır fakat biz bu terkibi gerek konuyu daha anlaşılır kılması gerek ifadenin bir cümleden ziyade daha pratik kullanımına yol açması bakımından kullanmayı uygun gördük. Meseleyi araştırmaya layık bulmamızın sebeplerinin başında, onunla alakalı müstakil ve özgün çalışmaların neredeyse yok denecek kadar az olması gelmektedir. Diğer bir sebep, kendisine sıkça ve açıkça fırsat tanımayanların onu istishâb başlığı altında incelemesi hasebiyle ikisi arasındaki ilişkiyi belirlemek olmuştur. Bu süreç içerisinde multidisipliner okuma eğilimimiz, konuya ilişkin modern mantıkta da boy gösteren bazı terimsel ifadelerin ne denli benzer olduğunu fark etmemize yol açtı. İslam hukuk metodolojisinde dinî hükümleri ilgili kaynaklardan çıkartacak uzmanlar için temel yöntemlerin bilinmesinde önemli bir rol oynayan “kanıt yokluğu/nefyü’l-medârik” metodu daha çok istishâb deliliyle beraber ele alınmış ve müstakil bağlamda incelenmemiştir. Herhangi bir konuyla alakalı onun hükmünü oluşturacak delilin bulunmaması durumunda hukukçular, delil yok diye hükmün de olmadığını belirten bu yöntemden bahsetmişlerdir. Genellikle Hanefîler’in fasid deliller başlığı altında inceledikleri kanıt yokluğu meselesi, yer yer diğer hukukçular arasında kullanılmıştır. Şayet delilin yokluğu sebebiyle hükmün yokluğuna karar verilmezse, âlimlerin burada istishâb deliline başvurarak hükmün varlığının devam ettiğine dair kanaatleri oluşmuştur. Ancak, dile getirdiğimiz üzere her iki yöntemin karışık biçimde ele alınışı onların hiyerarşik deliller platformunda nereye konumlanacakları ve nasıl algılanacakları problemini doğurmuştur. Beş vakit namazın varlığının gerekliliği üzerine altıncı bir vakit namazın emredilmediği gerçeği nefy yöntemine ait belli örneklerin başında gelmektedir. Buna göre, kanun koyucunun beş vaktin üzerine bir yenisini koymadığını ve tam tersi şekilde koyduğunu gösteren herhangi bir delilin bulunmamasıyla da altıncı vakit namazın yokluğuna hükmetmek mevzu bahistir. Delil yokluğu konusu, kapsamı bakımından sadece klasik fıkıhta kullanılmamaktadır. Hatta bu konunun genişliğini sadece İslâmî ilimlerle sınırlamamak gerekir. Öyle ki delil yokluğu yöntemi, modern bilim anlayışına da yön vermektedir. Daha çok kanıt yokluğu şeklinde dile getirilen söz konusu yöntem hiç de azımsanmayacak sayıya ulaşmış bir popüler kabulle reddedilmektedir. Tabiri caizse bilim, kanıt yokluğunu doğru bir yaklaşım olarak görmemektedir. Kanıt yokluğunun verilen meşhur ve çarpıcı bir örneği şu şekildedir: “Dünyada uzaylıların varlığı gösteren herhangi bir kanıt yoktur, öyleyse bunu gösteren bir kanıt olmamasına dayanarak uzaylılar yoktur veya uzaylıların varlıkları yoktur”. Bu çalışmamızda öncelikle delil yokluğu tamlamasını oluşturan unsurlar incelenmiştir. Delil yokluğu yöntemi, inceleme sonucu oluşan anlam bakımından tartışmaları ve taraflarıyla beraber ele alınmıştır. Kendisiyle bulunduğu ilgisi açısından istishâbla olan ilişkisi irdelenmiştir. Bunu yaparken ilgili delilin yokluğundan ötürü hükmün de bulunmadığını iddia eden kimsenin salt bir şekilde iddiasını ispatlatmasının yeterli olup olmadığına da yer verdik. Tüm bunları ortaya koymaya çalışırken, delil yokluğu yönteminde ilgili hükme dair delilin bulunmadığını iddia eden kişinin salt şekilde buna dayanarak karar vermesinin ne kadar doğru olup olmadığına da değinmeye çalıştık. Ayrıca delil yokluğu konusunu, ilgisi olması hasebiyle kelam ve mantık gibi çeşitli disiplinlerin bazı meseleleriyle beraber ele aldık. Yapılan tartışmalar sonucunda, nefy metodu ile istishabın aynı şeyler olmadığını ortaya koymaya çalıştık. Bunların ardından nefy teorisi hakkında birtakım değerlendirmeler yapılmıştır. Söz konusu değerlendirmeler arasında, daha çok Hanefîlerin bu konuda takındığı tavra yakın birtakım yorumlar ve mantık ilmi yönünden nefyin yanlışlığına dair tespitler bulunmaktadır. Sonuçta nefyü’l-medârike ait müstakil bir çalışma, ona dair yapılan mantıksal bir yaklaşımdan güç alarak siz okuyucuların arzına sunulmuş oldu. Ne var ki bu girişim, konumuza ait literatürdeki boşluğu tam anlamıyla doldurmayacaktır. Umarız elinizdeki çalışma, zikri geçen boşluğu doldurma amacıyla yapılacak olan diğer başka araştırmalara vesile olarak konunun daha geniş kitlelere ulaşmasına hizmet eder.
Fıkıh Usûlünde Nefyü’l-Medârik Yöntemine Mantıkî Bir Yorum
Keywords: Islamic Law; İslam Hukuku